The Effects of Endocrine Disruptors on Adipogenesis and Osteogenesis in Mesenchymal Stem Cells: A Review - Bateman, Marjorie E.; Strong, Amy L.; McLachlan, John A.; Burow, Matthew E.; Bunnell, Bruce A. (Frontiers in Endocrinology, 2017)
Endocrine disrupting chemicals (EDCs) are prevalent in the environment, and epidemiologic studies have suggested that human exposure is linked to chronic diseases such as obesity and diabetes. In vitro experiments have further demonstrated that EDCs promote changes in mesenchymal stem cells (MSCs), leading to increases in adipogenic differentiation, decreases in osteogenic differentiation, activation of pro-inflammatory cytokines, increases in oxidative stress, and epigenetic changes. Studies have also shown alteration in trophic factor production, differentiation ability, and immunomodulatory capacity of MSCs, which have significant implications to the current studies exploring MSCs for tissue engineering and regenerative medicine applications and the treatment of inflammatory conditions. Thus, the consideration of the effects of EDCs on MSCs is vital when determining potential therapeutic uses of MSCs, as increased exposure to EDCs may cause MSCs to be less effective therapeutically. This review focuses on the adipogenic and osteogenic differentiation effects of EDCs as these are most relevant to the therapeutic uses of MSCs in tissue engineering, regenerative medicine, and inflammatory conditions. This review will highlight the effects of EDCs, including organophosphates, plasticizers, industrial surfactants, coolants, and lubricants, on MSC biology.